A theoretical discussion about curriculum and disability: Implications for teaching conceptions and practices (Research, Society and Development, 2021)
This article aims to discuss ways of curricular organization in attention to the needs of students with disabilities, global developmental disorders, and high skills/giftedness, target audience of special education, with a focus on teaching concepts and practices. To this end, it is based on a state-of-the-art methodology on curriculum and special education regarding the 2015-2019 interval at the Brazilian Digital Library of Theses and Dissertations (BDTD). The theoretical survey, derived from Scientific Initiation research at the Universidade do Estado da Bahia (2019-2020), cooperates for the understanding about a common and accessible curriculum for all students and its reverberations in teaching practices for inevitably heterogeneous classes, mainly in the conception of basic deficiency for the engendering of these practices. Regarding the categories identified in the research a) broad conception and b) individualized conception, it is noted the separation of the following quantitative: of the total of 32 studies analyzed, 7 studies are based on the broad conception and 25 works are based on the individualized conception. The prevalence of studies from the perspective of an individualized curricular concept arouses attention and, under the aspects marked out in this text, indicate the importance of expanding the idea of the same curriculum accessible to any students. Undoubtedly, the dissemination of the study can favor the field of inclusion of the target audience of special education, especially because it inspires future research and experiences to guarantee this school inclusion.